2016
DOI: 10.1021/acschemneuro.6b00150
|View full text |Cite
|
Sign up to set email alerts
|

TANGO-Inspired Design of Anti-Amyloid Cyclic Peptides

Abstract: β-Amyloid peptide (Aβ) self-associates into oligomers and fibrils, in a process that is believed to directly lead to neuronal death in Alzheimer’s disease. Compounds that bind to Aβ, and inhibit fibrillogenesis and neurotoxicity, are of interest as an anti-Alzheimer therapeutic strategy. Peptides are particularly attractive for this purpose, because they have advantages over small molecules in their ability to disrupt protein–protein interactions, yet they are amenable to tuning of their properties through che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 47 publications
(114 reference statements)
3
37
0
4
Order By: Relevance
“…cG8b was purified by RP-HPLC on a Vydac C18 column as previously described. [15] ThT analysis confirmed that cG8b retained the ability to inhibit Aβ aggregation (data not shown).…”
Section: Methodsmentioning
confidence: 82%
See 4 more Smart Citations
“…cG8b was purified by RP-HPLC on a Vydac C18 column as previously described. [15] ThT analysis confirmed that cG8b retained the ability to inhibit Aβ aggregation (data not shown).…”
Section: Methodsmentioning
confidence: 82%
“…[13, 15] In this study, we evaluated mTTR and cG8 for their efficacy, stability, selectivity and mode of action. Our aim was to compare critical parameters that influence the choice of protein versus peptide-based compounds for anti-amyloid therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations